RANCANG BANGUN SISTEM ADMINISTRASI JASA LAUNDRY DENGAN METODE WATERFALL - . Sunarti (Paradigma, 2014)
For the implementation of administrative processes requires a computerized administration system for data and information can be processed properly. Administrative information systems strategic planning sales laundry services will provide a comprehensive picture of the needs of the administrative information system established by the company. This research aims to produce results from the administrative information systems strategic planning sales laundry services, where the research was conducted on the apartment rental service company in Plaza Senayan Apartment degan using Visual Basic.NET. Data collection was performed by the method of literature review, interviews and observation. Systems development method of information system using the waterfall method, in describing the functional model and ERD (Entity Relationship Diagram) to describe the data model. Research conducted through several stages, namely the study of literature, determination of the general method, administrative information systems strategic planning, laundry services, analysis and conclusions as a system design that will be created. The results of this study provide information on entry and exit laundry process quickly, precisely and accurately, giving the proposed computerized system to the laundry which is expected to ease the work of the staff room and can speed up the search process the data, minimizing errors and loss of data, as well as speed up the reporting process. Keywords : Design, Laundry Services, Waterfall